Types of intellectual capital employed in bioeconomic projects: A longitudinal case study - Maria-Silvia Săndulescu; Dragoş Andrei Stoica; Cătălin-Nicolae Albu; Nadia Albu (Amfiteatru Economic Journal, 2018)
In this paper we investigate the existence and evolution of bioeconomic projects of OMV Group, a major global player in the oil and gas industry. We further study the intellectual capital components utilized by OMV Group in supporting these bioeconomic actions. We conduct a longitudinal case study over the 2010-2016 period and illustrate with the case of OMV Group how the oil and gas organizations mobilize various types of intellectual capital to engage in bioeconomic projects. Since the global importance of bioeconomy increased exponentially in the last years, we employ a theoretical framework recently proposed in the bioeconomic literature to ascertain the type of vision followed in the bioeconomic projects and its evolution. We find that the number of bioeconomic projects proposed by our case organization increased over time, and that the projects' focus evolved from bio-technology and bio-resources to bio-ecology, which has the potential of providing more long-term sustainable outcomes.
Keywords: Q57; L65; Q16; O34; 330; bioeconomy; intellectual capital; innovation; sustainability; oil and gas industry